ATP-activated P2X7 receptor in the pathophysiology of mood disorders and as an emerging target for the development of novel antidepressant therapeutics. (April 2018) - Wei, Linyu; Syed Mortadza, Sharifah A; Yan, Jing; Zhang, Libin; Wang, Lu; Yin, Yaling; Li, Chaokun; Chalon, Sylvie; Emond, Patrick; Belzung, Catherine; Li, Dongliang; Lu, Chengbiao; et al.
Highlights: Innate immune system dysfunction plays a critical role in the pathology of mood disorders. ATP-activated P2X7 receptor is a key player in innate immune response. SNPs in human P2X7 gene are associated with predisposition to mood disorders. Rodent behaviour studies support an important role of P2X7 receptor in stress-induced depressive-like, manic-like and anxiety-like behaviours. CNS-penetrable P2X7 antagonists are under development as brain inflammation imaging tracers and antidepressant therapeutics. Abstract: Mood disorders are a group of psychiatric conditions that represent leading global disease burdens. Increasing evidence from clinical and preclinical studies supports that innate immune system dysfunction plays an important part in the pathophysiology of mood disorders. P2X7 receptor, belonging to the ligand-gated ion channel P2X subfamily of purinergic P2 receptors for extracellular ATP, is highly expressed in immune cells including microglia in the central nervous system (CNS) and has a vital role in mediating innate immune response. The P2X7 receptor is also important in neuron-glia signalling in the CNS. The gene encoding human P2X7 receptor is located in a locus of susceptibility to mood disorders. In this review, we will discuss the recent progress in understanding the role of the P2X7 receptor in the pathogenesis and development of mood disorders and in discovering CNS-penetrable P2X7 antagonists for potential uses in in vivo imaging to monitor brain inflammation and antidepressant therapeutics.